2020
DOI: 10.7717/peerj.8569
|View full text |Cite
|
Sign up to set email alerts
|

Tight DNA-protein complexes isolated from barley seedlings are rich in potential guanine quadruplex sequences

Abstract: Background The concept of chromatin domains attached to the nuclear matrix is being revisited, with nucleus described as a set of topologically associating domains. The significance of the tightly bound to DNA proteins (TBP), a protein group that remains attached to DNA after its deproteinization should be also revisited, as the existence of these interactions is in good agreement with the concept of the topologically associating domain. The work aimed to characterize the DNA component of TBP is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Many G4-binding proteins in animals and humans are known [ 43 ]. Recently, it has been shown that proteins in barley seedlings can bind to PQSs and form DNA–protein complexes [ 44 ], so we can expect that G4-binding proteins also will be present in plant genomes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many G4-binding proteins in animals and humans are known [ 43 ]. Recently, it has been shown that proteins in barley seedlings can bind to PQSs and form DNA–protein complexes [ 44 ], so we can expect that G4-binding proteins also will be present in plant genomes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 Research studies on Hordeum vulgare (Barley) clearly state that the DNA-binding proteins in barley seedlings are rich in potential G-quadruplexes, although the genome is rich in i-motifs. 18 . Previous research on rice plants justifies that the G-motifs were higher in monocotyledon plants than dicotyledons.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al described the binding of the protein, JULGI, to RNA G4 located in 5’UTR of the SMXL4 and SMXL5 genes inhibiting their translation [ 20 ]. Additionally, Sjakste et al analyzed the sequences of DNAs that were tightly bound to the proteins in barley seedlings [ 21 ]. They found that the sequences that were bound by these proteins were highly enriched in GC content, compared to the rest of the barley genome, and CD spectroscopy confirmed that JULGI-bound sequences are able to form G4s [ 20 ].…”
Section: Introductionmentioning
confidence: 99%